2019
DOI: 10.1136/bmj.l4280
|View full text |Cite
|
Sign up to set email alerts
|

Rising rates of colorectal cancer in younger adults

Abstract: Worsening diet, obesity, and lack of exercise are probable major contributors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The reasons underlying the marked increase in incidence in those aged under 50 years are not clear, but may relate to lifestyle factors, particularly around diet, body weight and physical activity, all of which are associated with increased risk of CRC. 20 Rising rates of obesity in younger life (which are indicators of diet and physical activity) are of particular interest, because excess adiposity is now experienced by more people at earlier life stages and a recent study has demonstrated a relationship between body mass index in childhood and risk of adult CRC. 21 We cannot necessarily screen our way out of this problem.…”
Section: Open Accessmentioning
confidence: 99%
“…The reasons underlying the marked increase in incidence in those aged under 50 years are not clear, but may relate to lifestyle factors, particularly around diet, body weight and physical activity, all of which are associated with increased risk of CRC. 20 Rising rates of obesity in younger life (which are indicators of diet and physical activity) are of particular interest, because excess adiposity is now experienced by more people at earlier life stages and a recent study has demonstrated a relationship between body mass index in childhood and risk of adult CRC. 21 We cannot necessarily screen our way out of this problem.…”
Section: Open Accessmentioning
confidence: 99%
“…According to the 2020 Global Cancer Statistics Report Interpretation [1], colorectal cancer (CRC) is expected to be the 3rd in the global incidence spectrum and the 2nd in the cause of death spectrum among new cancers worldwide in 2020, and the rate of death continues to increase. Potter John D (2020) [2] found that the standardized incidence and mortality rates of CRC are higher in men than in women, and the number of colorectal cancers has increased among young people. And recurrence and metastasis of colorectal cancer after surgery are the main causes of death of patients.…”
Section: Introductionmentioning
confidence: 99%
“…In the Netherlands, colorectal cancer (CRC) is one of the most commonly diagnosed cancers with around 11,700 new cases in 2020 [1]. Increased incidence of CRC among young adults (50 years of age and younger) has recently been reported [2,3]. In women, the lifetime risk of developing CRC (4.1%) is slightly lower than for men (4.4%) [4].…”
Section: Introductionmentioning
confidence: 99%